Impact of Low-Dose Hydrocortisone on the Incidence of Atrial Fibrillation in Patients With Septic Shock: A Propensity Score-Inverse Probability of Treatment Weighting Cohort Study. (March 2019) - Launey, Yoann; Lasocki, Sigismond; Asehnoune, Karim; Gaudriot, Baptiste; Chassier, Claire; Cinotti, Raphael; Maguet, Pascale Le; Laksiri, Leila; Mimoz, Olivier; Tawa, Audrey; Nesseler, Nicolas; Malledant, Yannick; et al.
Purpose: Atrial fibrillation (AF) is common in the intensive care unit (ICU), notably in patients with septic shock for whom inflammation is an already identified risk factor. The aim of this study was to evaluate the effect of low-dose hydrocortisone on AF occurrence in patients with septic shock. Methods: We performed a prospective nonrandomized observational study in 5 academic ICUs in France. From November 2012 to June 2014, all patients ≥16 years having septic shock were included, except those who had a history of AF, had a pacemaker, and/or experienced AF during hospitalization before the onset of shock or in whom the onset of shock occurred prior to admission to the ICU. Hydrocortisone was administered at the discretion of the attending physician. The incidence of AF was compared among patients who received hydrocortisone, and the effect of low-dose hydrocortisone on AF was estimated using the inverse probability treatment weighting method based on propensity scores. Results: A total of 261 patients were included (no-hydrocortisone group, n = 138; hydrocortisone group, n = 123). Atrial fibrillation occurred in 57 (22%) patients. Atrial fibrillation rates were 33 (24%) and 24 (19%) in no-hydrocortisone patients and hydrocortisone patients, respectively. In the weighted sample, the proportion of patients who developed AF was 28.8% in the no-hydrocortisone group and 16.8% in the hydrocortisone group (difference: −11.9%; 95% confidence interval: −23.4% to −0.5%; P = .040). Conclusion: In patients with septic shock, low-dose hydrocortisone was associated with a lower risk of developing AF during the acute phase.